Bladder training and Kegel exercises for women with urinary complaints living in a rest home - (:unkn) unknown (KARGER, 2008)
Background: Urinary incontinence is an annoying, uncomfortable and unpleasant condition affecting the elderly. The problem of bedwetting and other urinary complaints are common in rest homes. Objective: Our study aimed to determine the efficiency of bladder training and Kegel exercises for older women living in a rest home. Methods: This is an experimental prospective research study. Through a randomization process, 25 women were included in the treatment group, and another 25 were included in the control group. Participants were living in a rest home for women aged older than 65 years with urinary complaints. The pretreatment interview form, Quality of Life Scale, Mini-Mental Test, Rankin Scale, daily urinary forms and pad tests were administered to the treatment and control groups. Bladder training and Kegel exercises were given to the treatment group for 6-8 weeks. The second evaluation was performed 8 weeks after treatment, and the last evaluation was carried out 6 months after treatment. Results: The average age of the treatment group was 78.88 +/- 4.80 years, and the average age of the control group 79.44 +/- 5.32 years. Urgency, frequency and nocturia were common complaints. Pretreatment, 8-week and 6-month evaluations revealed that the amount of urinary incontinence with urgency, frequency and nocturia complaints statistically and significantly decreased in the treatment group compared to the control group. In the pad test results, a statistically significant decrease was observed in the treatment group compared to the control group. A significant increase in pelvic floor strength was observed in the treatment group compared to the control group upon all evaluations. Conclusion: Behavioral therapy can be used easily as an effective treatment for urinary incontinence in elderly women living at a rest home. Copyright (C) 2008 S. Karger AG, Basel.
Keywords: urinary incontinence; bladder training; Kegel exercises; old age; INCONTINENCE; PREVALENCE; EFFICACY